The Effect of Discovery Learning with the Scaffolding Method on Science Literacy Ability and Student Motivation in terms of Academic Ability - Nofiyanti Safitri; Dwi Oetomo; Slamet Santosa (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
This study aims to 1) The influence of discovery learning model with scaffolding toward the scientific literacy and student’s learning motivation, 2) the influence of academic ability toward scientific literacy and student’s learning motivation, 3) The interaction between learning models and academic abilities on scientific literacy and student motivation.This research is a quasi-experimental research type. The research design used in this study was Postest only nonequivalent design. This research was conducted at SMAN 5 Surakarta as a research subject. The sampling technique used in this study is cluster random sampling. The instrument used in this study used a questionnaire instrument to measure learning motivation and scientific literacy test questions using indicators from NOSLiT. The data analysis technique used is Two Way Analysis of Variance. The results of the study (1) the learning modeldiscovery learning accompanied by scaffolding has an effect on scientific literacy and student learning motivation, (2) students' academic ability has an effect on scientific literacy competence, and (3) there is no interaction between discovery learning and scaffolding learning models in terms of academic ability on scientific literacy skills, and learning motivation.